2001
DOI: 10.1046/j.1365-2788.2001.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Cause-specific mortality of people with intellectual disability in a population-based, 35-year follow-up study

Abstract: The aim of the present study was to investigate cause-specific mortality in people with intellectual disability (ID). It was based on a 35-year follow-up study of a nation-wide population of 2369 subjects aged between 2 and 97 years. The 1095 deceased people had accumulated 64 539 person-years. The research took the form of a prospective cohort study with mortality follow-up. Observed and expected deaths were calculated as standardized mortality ratios using the Finnish general population as the reference. Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
122
4
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 12 publications
8
122
4
1
Order By: Relevance
“…Most patients within this group died owing to pneumonia. High mortality due to pneumonia has often been connected to mental retardation (24) and seriously ill infants, as was the case in our study.…”
Section: Causes Of Sudden and Cardiovascular Deathssupporting
confidence: 75%
“…Most patients within this group died owing to pneumonia. High mortality due to pneumonia has often been connected to mental retardation (24) and seriously ill infants, as was the case in our study.…”
Section: Causes Of Sudden and Cardiovascular Deathssupporting
confidence: 75%
“…No association with cancer was found in the earlier studies in Lecistershire, 122 nor was it found a large 35-year follow-up study in Finland. 15 Although we found a small excess of mortality from cancer in adults with ID in our study, it varied by type, and was notably smaller for lung and prostate cancer. Cancer is thought to be a less prominent cause of death for people with ID, perhaps owing to the premature mortality within this group.…”
Section: Mortalitycontrasting
confidence: 61%
“…Local ID register-based studies have identified markedly higher mortality, with estimates in the age-adjusted risk of death ranging between 3 and 18 times higher than those of the general population. 5,15,16 This increased risk of death is seen across a range of conditions and is not limited to causes related to the underlying ID. Studies on disease prevalence and morbidity among people with ID, although limited, provide a similar picture, with an increased risk of epilepsy, diabetes, cardiovascular disease, infections, accidents and sensory impairment.…”
Section: Health Of People With Intellectual Disabilitymentioning
confidence: 99%
“…It has been known for several decades that individuals who are severely cognitively impaired have increased rates of mortality in childhood, adolescence (Simila, von Wendt, & Rantakallio, 1986) and adulthood (Patja, Molsa, & Iivanainen, 2001;Patja, Iivanainen, Vesala, Oksanen, & Ruoppila, 2000). More recently, attention has been focussed on the inverse association of childhood cognition with mortality in adult life that appears to extend over the entire range of IQ (Batty, Deary, & Gottfredson, 2007).…”
Section: Introductionmentioning
confidence: 99%